Atrophy of mammillary bodies in early stages of Alzheimer's disease. (December 2021) - Tao, Alice; Pan, Yushan; Myslinski, Zachary; Iadecola, Costantino; Dyke, Jonathan; Chiang, Gloria; Ishii, Makoto
Abstract: Background: The mammillary bodies (MB) share direct connections with key components of memory circuitry including the hippocampus. Additionally, MB atrophy is present in a number of clinical conditions including late stages of Alzheimer's disease (AD); however, whether MB atrophy occurs in early stages of AD remains unclear. Voxel‐Based Morphometry (VBM) was conducted to determine whether structural changes to MB are an early feature of AD and to quantify the association between MB atrophy and performance on neurocognitive assessments. Method: This cross‐sectional study included subjects (n=470) from the Alzheimer's Disease Neuroimaging Initiative aged ≥ 50 years with volumetric T1‐weighted MR scans at 3 Tesla and cerebrospinal fluid (CSF) AD biomarkers. Normal cognition (cognitively normal, CN, and preclinical AD) was defined as Clinical Dementia Rating (CDR) of 0. Based on previously established criteria, CN subjects (n=112) were negative for CSF AD pathology, while preclinical AD (n=39), early mild cognitive impairment (EMCI, n=108), late mild cognitive impairment (LMCI, n=100), and AD (n=111) subjects were positive for CSF AD pathology. Average grey matter (GM) densities in the MB, hippocampus, and cerebellar vermis were assessed by VBM (SPM12 with MarsBaR toolbox). Result: GM densities in MB and hippocampi decreased with worsening clinical severity with significant differences beginning in the EMCI stage for both regions. Compared to CN subjects, the relative decrease in GM densities was greater in MB than in the hippocampi in EMCI, LMCI, and AD subjects. Cerebellar vermian GM densities were similar across all groups. Adjusting for age and sex, MB GM densities were associated with CSF levels of amyloid‐β42 (β=0.189, p<0.001) but not with tau or phosphorylated‐tau181 (p>0.05). Hippocampal GM densities were associated with all CSF AD biomarkers (p<0.05). Adjusting for age, sex, and education, MB and hippocampal GM densities were associated with Mini‐Mental State Examination (MB: β=0.270, p<0.001, hippocampi β=0.512, p<0.001) and CDR Sum of Boxes (MB: β=‐0.337, p<0.001, hippocampi: β=‐0.561, p<0.001). Conclusion: Evidence for MB atrophy was found in early stages of AD and increased with clinical severity, correlating with CSF amyloid‐β42 and neurocognitive measures. These findings support MB atrophy as an early manifestation of AD.